Percutaneous Emergency Needle Caecostomy for Prevention of Caecal Perforation. (15th August 2017) - Limmer, Alexandra M.; Clement, Zackariah
Abstract : Caecal perforation is a life-threatening complication of large bowel obstruction with a reported mortality of 34% to 72%. This case describes the novel use of percutaneous needle caecostomy as a life-saving measure to prevent imminent caecal perforation in a 68-year-old lady with large bowel obstruction secondary to an incarcerated incisional hernia. After careful review of computed tomography images and measurement of distances from the abdominal wall to the caecum, the patient's caecum was decompressed in the emergency department using a needle under local anaesthetic. The patient subsequently underwent laparoscopic hernia repair and had an uncomplicated recovery. When conducted safely and with precision in an appropriate patient, percutaneous needle caecostomy can provide immediate symptom relief, reduce risk of caecal perforation, and allow a laparoscopic surgical approach.